2005
DOI: 10.1590/s1516-44462005000100013
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of psychiatric diagnosis performed under indirect supervision

Abstract: Abstract Abstract Abstract This work aimed at comparing the accuracy of the psychiatric diagnoses made under indirect supervision to the diagnoses obtained through Structured Clinical Interview for DSM-III-R (SCID O objetivo deste estudo foi comparar a precisão do diagnóstico psiquiátrico elaborado sob supervisão indireta com o diagnóstico obtido por meio da Entrevista Clínica Estruturada para o DSM-III-R (SCID). O estudo foi realizado em três serviços universitários (ambulatório, enfermaria e emergência). Os … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
(7 reference statements)
0
16
0
1
Order By: Relevance
“…The Structured Clinical Interview from the DSM-IV, clinical version (SCID-CV) (12), translated into Portuguese (13,14), was administered for the confirmation of the diagnosis of SAD. Participants who presented other psychiatric disorders were excluded, except for those with past depressive episodes because depression is frequently comorbid with SAD.…”
Section: Participantsmentioning
confidence: 99%
“…The Structured Clinical Interview from the DSM-IV, clinical version (SCID-CV) (12), translated into Portuguese (13,14), was administered for the confirmation of the diagnosis of SAD. Participants who presented other psychiatric disorders were excluded, except for those with past depressive episodes because depression is frequently comorbid with SAD.…”
Section: Participantsmentioning
confidence: 99%
“…The interview is commonly conducted face-to-face and its duration varies as a function of the presence of symptoms to be investigated. The accuracy of SAD diagnoses obtained through structured interviews has been evaluated, and the results obtained thus far show that the reliability of SAD diagnoses obtained with the original version of the SCID, as well as with versions adapted and translated into other languages, reaches satisfactory levels (Aziz & Kenford, 2004;Del-Ben et al, 2005;Lyneham & Rapee, 2005). Although the SCID was developed to be used face-to-face, interviews in research settings (such as screening for epidemiological surveys) have also been carried out by telephone (Aziz & Kenford, 2004;Carlbring et al, 2007).…”
Section: Structured Clinical Interview For Dsm-iv (Scid-iv)mentioning
confidence: 99%
“…20 Along these lines, we have observed that the use of operational diagnostic criteria and the training in the application of the SCID have increased the reliability of diagnoses performed in psychiatric emergency assessments. 22 …”
Section: Accuracy Of the Diagnosis Of First-episode Psychosismentioning
confidence: 99%